The development potential of migration: The status quo, lessons from other regions, and implications for research - Naudé, Wim; Maystadt, Jean-François; de Brauw, Alan; Lucas, Robert E.B.; Gubert, Flore; Wouterse, Fleur Stephanie; de Haas, Hein (International Food Policy Research Institute, 2013)
This issue of the Thematic Research Notes discusses the causes and impact of migration among communities in Africa as well as predicted future migration trends.